2021
DOI: 10.3390/vaccines9030241
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccines in the Pipeline, Are Antibodies Adequate?

Abstract: The COVID-19 pandemic caused by the novel coronavirus strain SARS-CoV-2 has already led to catastrophic consequences in global physical and psychological health, as well as economic recession [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Although Rappouli et al [3] reported that the development of a human vaccine could take at least 15 years and at least USD 200 million, an alliance of the science society has now achieved this [4]. Besides the hesitation on the authenticity and reported side-effects in a small proportion of people of approved vaccines [141,142], the worldwide vaccination is time consuming, as well as public health being in danger from current virus mutations, which can lead to a prolonged pandemic leading towards a difficult situation [143]. In this rapidly evolving crisis, drug repurposing is considered the quickest way to identify potential drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although Rappouli et al [3] reported that the development of a human vaccine could take at least 15 years and at least USD 200 million, an alliance of the science society has now achieved this [4]. Besides the hesitation on the authenticity and reported side-effects in a small proportion of people of approved vaccines [141,142], the worldwide vaccination is time consuming, as well as public health being in danger from current virus mutations, which can lead to a prolonged pandemic leading towards a difficult situation [143]. In this rapidly evolving crisis, drug repurposing is considered the quickest way to identify potential drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A novel strain of coronavirus, SARS-CoV-2, the causative agent of coronavirus disease (COVID-19) was first associated with severe acute respiratory disease in late 2019 and has triggered an ongoing pandemic since March 2020 [1][2][3]. The pandemic has already had a serious impact on the global economy and has resulted thus far, to over 2.7 million deaths and over 122 million infections [4].…”
Section: New Sars-cov-2 Mutantsmentioning
confidence: 99%
“…Manufacturing clinical-grade mRNA is also a challenging task. With the emergence of the recent COVID-19 pandemic, a significant number of DNA (26 candidates) and mRNA (35 candidates) vaccines (Table 1) are in preclinical and clinical trials despite these limitations, and eventually, two vaccines have been approved from the mRNA platform for mass application [125,126], and one from DNA platform, i.e., ZycovD (Zydus Cadila, India), has been approved [104]. The Pfizer-BioNTech and Moderna vaccines have demonstrated very good efficacy and safety in human trials, despite the evidence of increased risk of blood clots in a small number of subjects.…”
Section: Challenges For Nucleic Acid Vaccine Developmentmentioning
confidence: 99%
“…However, the long-term safety, vaccine stability and efficacy still need to be established for this platform and is a subject matter of future studies. The efficacy of nucleic acid-based vaccines is hindered by viral mutations, and the approved mRNA vaccines have demonstrated variable reduced efficacy against these mutant strains as compared with the efficacy against original non-mutated strains [125,126]. As viruses are known to mutate, mutations will continue with the SARS-CoV-2 virus, and hence, constant modifications of the vaccine are required to be effective against the new variants.…”
Section: Challenges For Nucleic Acid Vaccine Developmentmentioning
confidence: 99%